Heathcliff e Becky Sharp: a recusa à conformidade associada ao mal - Santos, Paulo Victor Mascarenhas dos (2023)
The goal of this work is to analyze the characters Heathcliff, from Wuthering Heights (written by Emily Brontë), and Becky Sharp, from Vanity Fair (written by William Makepeace Thackeray), characters of two literary works that show proximity in time and space, both being English novels published in the nineteenth century. Using the comparative method, the idea of the study is to observe which aspects of these characters make them transgressive to the standards of their society, and how this transgressive aspect makes other characters from their novels, and even some critics and readers, associate Heathcliff and Becky with the concept of evil. It was relevant to this research to study the effects of the racist and sexist oppression that affected people like the characters in question, and how this oppression contributed to Heathcliff and Becky, in a marginalized position, having to fight to have a dignified existence. To reach the goal of this work, the concept of evil itself was studied under the optics of morality, conversing with names such as Nietzsche, Paul Ricoeur, St. Augustine and Hannah Arendt, as well as the way this morality can be applied to literary characters, using the considerations of authors such as James Wood, Antonio Candido and Roland Barthes. There were also analysis of several aspects of the historical and social context in which the characters were inserted, as well as characteristics of Heathcliff and Becky that present a difficulty in classifying them as just good or evil. There was also a direct comparison between the trajectory of the two characters, and how their similarities and differences demonstrate how people with their physical and social characteristics were treated at the time of their respective novels. This direct research about the characters conversed with the considerations of researchers such as Sylvia Iwami, Virginia Bledsoe, Daise Dias, Verônica Lage, among others.